1.已知f(x+1/x)=(x^3)+1/x^3..求f(x)2.已知f(2/x +1)=lgx ..求f(x)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 20:46:12
1.已知f(x+1/x)=(x^3)+1/x^3..求f(x)2.已知f(2/x+1)=lgx..求f(x)1.已知f(x+1/x)=(x^3)+1/x^3..求f(x)2.已知f(2/x+1)=lg
1.已知f(x+1/x)=(x^3)+1/x^3..求f(x)2.已知f(2/x +1)=lgx ..求f(x)
1.已知f(x+1/x)=(x^3)+1/x^3..求f(x)
2.已知f(2/x +1)=lgx ..求f(x)
1.已知f(x+1/x)=(x^3)+1/x^3..求f(x)2.已知f(2/x +1)=lgx ..求f(x)
1:设 x+1/x=y
则有 x^3+1/x^3=(x+1/x)^3-3(x+1/x)=y^3-3y
f(x+1/x)=x^3+1/x^3可以变换为f(y)=y^3-3y
即 f(x)=x^3-3x
2:令t=2/x+1,则x=2/(t-1)
代入得f(t)=lg(2/(t-1))
所以f(x)=lg(2/(x-1))
1题用整体替换,配凑法
f(x+1/x)=(x^3)+1/x^3
=(x+1/x)(x^2-1+1/x^2)
=(x+1/x)[(x+1/x)^2-3]
∴f(x)=x(x^2-3)
2题可用换元法,
令2/x+1=t,t≠1
x>0,
解得x=2/(2-t)
∴f(t)=lg[2/(2-t)],
∴f(x)=lg[2/(2-x)],x>1
已知f(x)满足2f(x)+f(1/x)=3x,求f(x)
已知f(x)满足2f(x)+f(1/x)=3x,求f(x)?
已知f(x)满足2f(x)+f(-x)=-3x+1,求f(x)
已知f(x)满足f(x)+2f(1/x)=3x,求f(x) ,
1.已知f(x+1/x)=(x^3)+1/x^3..求f(x)2.已知f(2/x +1)=lgx ..求f(x)
已知f(x+1/x-1)=3f(x)-2x,求f(x)
已知函数f(x)=x^3+x^2-2x-x,f(1)f(2)
已知f(x)+2f(1/x)=x+2/x+3,求f(x)
1.已知f(x+2)=3x-2,求f(x)=?2.已知a×f(x)+f(1/x)=ax,求f(x)=?
1.已知f(x)=3-4x/2x+1,不等式f(x)
1.f(x)=x/(x^2+1),求f(1/x)2.已知f(x)=1-3x,求f(x)已知f(2x+1)=1-3x,求f(x)
(1) 已知f(x+1)=x*2+x,求f(x).(2)已知f(x-1/x)=(x+1/x)*2,求f(x) (3)已知f[f(x)]=2x)-1,求一次函数f(x)
1.已知等式f(x)+2f(1/x)=3x,求f(x) 2.设函数y=f(x)满足f(x)+2f(-x)=-x^2+2x,求函数y=f(x)
,已知5f(x)+3f(1/3)=2x+1.求f(x)
已知f(x)=(x-1)(x-2)(x-3)…(x-2008),求f’(1).
已知xf(x)-f(1-x)=-x的3次+x-1,求f(x)
已知f(x)=3x+1,x>=0,f(x)=x2,x
已知函数f(x)=2^-x(x大于等于3) f(x+1)(x